2006
DOI: 10.1080/09513590601005730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sports training in adolescence on growth, puberty and bone health

Abstract: Athletic training in adolescent females is important for their well-being; indeed, it may have both positive and negative effects on some physiological processes, as growth, reproductive axis and bone health. Adequate physical activity likely exerts neither a positive nor a negative effect on growth. By contrast, intensive training and insufficient diet may have a negative influence on growth, probably due to energy deficiency and impairment of the growth hormone-insulin-like growth factor-I axis; net long ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
13
0
2
Order By: Relevance
“…Depending on the nature of a sport and a girl's genetic descent, competitive sports lead to late menarche, especially when the kind of sport chosen requires much energy relative to body mass [18]. In girls who, in addition to having T1DM as a primary disease, practice their sport excessively, great ambition paired with a focus on attaining optimum weight for athletic competitions can increase the menarche-delaying effect of sports, which later manifests as impaired growth, menstrual dysfunction and low bone mass, known as the female athlete triad syndrome [4].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the nature of a sport and a girl's genetic descent, competitive sports lead to late menarche, especially when the kind of sport chosen requires much energy relative to body mass [18]. In girls who, in addition to having T1DM as a primary disease, practice their sport excessively, great ambition paired with a focus on attaining optimum weight for athletic competitions can increase the menarche-delaying effect of sports, which later manifests as impaired growth, menstrual dysfunction and low bone mass, known as the female athlete triad syndrome [4].…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, they showed that onset of menarche was later in the group with amenorrhea/oligomenorrhea than in the group with regular menstruation. Menstrual disorders and late onset menarche both seem to have caused by intensive training and inadequate energy intake [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…35,36 While there has been concern related to the effects of strenuous activity on bone density, studies have shown that regular weight-bearing activity actually increases the amount of bone mass gained during childhood, mainly at the bone sites which are trained. 37,38 Instead, the problem appears to be in young women in whom the combination of intensive training and inadequate energy intake lead to menstrual dysfunction. These girls manifest the "female athlete triad": 1) low energy availability, 2) amenorrhea, and 3) low bone mineral density.…”
Section: Bone Densitymentioning
confidence: 94%